2014
DOI: 10.1093/aepp/ppu033
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic and Fragmented Farm Supply Response for Second‐generation Bioenergy Feedstocks: Ex Ante Survey Evidence from Wisconsin

Abstract: Second‐generation bioenergy feedstocks stand poised to become a key component of the nation's agricultural and energy sectors, yet few studies have examined farm supply response using survey information. We use contingent valuation data from farmers in southwestern Wisconsin to develop ex ante supply estimates for two prospective feedstocks—corn stover and switchgrass—in terms of farmers' extensive and intensive acreage decisions. Supply response is found to be price inelastic and spatially fragmented, making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The same study found that around 30 percent of the surveyed farmers were willing to adopt switchgrass for energy production. Mooney et al (2015) employed a contingent valuation (CV) approach to investigate farmers' willingness to grow bioenergy crops on marginal lands in Southwest Wisconsin. Their findings show that marginal lands for bioenergy production are scarce and costly and potential spatial agglomeration of bioenergy production could arise.…”
Section: Introductionmentioning
confidence: 99%
“…The same study found that around 30 percent of the surveyed farmers were willing to adopt switchgrass for energy production. Mooney et al (2015) employed a contingent valuation (CV) approach to investigate farmers' willingness to grow bioenergy crops on marginal lands in Southwest Wisconsin. Their findings show that marginal lands for bioenergy production are scarce and costly and potential spatial agglomeration of bioenergy production could arise.…”
Section: Introductionmentioning
confidence: 99%
“…Swinton et al . defined marginal lands as the ‘farmable noncropland,’ and Mooney et al . defined marginal lands as the land ‘having one or more limiting soil characteristics, including poor drainage, shallow bedrock/water table, seasonal flooding, and excessive stoniness.’ After identifying marginal lands, these studies adopted a spatial sampling method to locate landowners who own the identified marginal lands to collect socioeconomic information by sending surveys.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of these two factors varies across different regions. Mooney et al . found that marginal land area has a positive effect on a landowner's initial decision on energy crop supply and, for landowners who are willing to supply energy crops, the marginal land area has a positive effect for landowners from southwestern Wisconsin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations